Transient dynamics and long-range transport of 2D exciton with managed potential disorder and phonon scattering - Wenqi Qian; Pengfei Qi; Yuchen Dai; Guangyi Tao; Haiyi Liu; Lie Lin; Zheyu Fang; Weiwei Liu (npj 2D Materials and Applications)
Abstract Two-dimensional excitons, characterized by high binding energy and valley pseudospin, are key to advancing photonic and electronic devices through controlled spatiotemporal dynamics of exciton flux. However, optimizing excitonic transport and emission dynamics, considering potential disorder and phonon scattering, requires further research. This study systematically investigates the effects of hexagonal boron nitride (hBN) encapsulation on semiconductor monolayers. Time-resolved photoluminescence (TRPL) and femtosecond pump-probe techniques reveal that encapsulation reduces excitonic radiative lifetime and enhances exciton-exciton annihilation, due to increased dielectric screening, which enlarges the Bohr radius and decreases binding energy. It also manages phonon scattering and thermal fluctuations, confirming non-monotonic temperature effects on emission and diffusion. The reduced disorder by hBN leads to a lowered optimized temperature from 250 K to 200 K, concurrently resulting in a doubled enhancement of the effective exciton diffusion coefficient. These findings highlight the importance of thermal and dielectric environmental control for ultrafast 2D exciton-based devices.